1982
DOI: 10.1002/ijc.2910300414
|View full text |Cite
|
Sign up to set email alerts
|

Natural cytotoxic cells against solid tumors in mice. IV. Natural cytotoxic (NC) cells are not activated natural killer (NK) cells

Abstract: Natural cell-mediated cytotoxicity (NCMC), measured against a variety of tumors, is mediated by at least two sub-populations of effector cells: natural cytotoxic (NC) and natural killer (NK). The studies described in this report show that target lysis by NC cells requires a prolonged (18- to 24 h) assay period, whereas NC-susceptible targets can be lysed in short-term (4h) [3H]-proline assays using allo-sensitized CTL or mitogen-activated cytotoxic populations. NC cells are not "activated" during the long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…MOLF/EiJ and PL/J exhibited low expression of all three NK specific cell surface markers such as NK1.1, Lgl-1, and NKG2A/C/E (data not included). Our results showing NK cell deficiency in peripheral blood obtained from PL/J mice correlated with previously reported decreased NK activity in the same strain (10). Interestingly, NZO/HlLtJ, NON/LtJ, and NZW/Lac/J, all members of group 3, had high percentages of NK cells (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…MOLF/EiJ and PL/J exhibited low expression of all three NK specific cell surface markers such as NK1.1, Lgl-1, and NKG2A/C/E (data not included). Our results showing NK cell deficiency in peripheral blood obtained from PL/J mice correlated with previously reported decreased NK activity in the same strain (10). Interestingly, NZO/HlLtJ, NON/LtJ, and NZW/Lac/J, all members of group 3, had high percentages of NK cells (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…We have previously shown that, whereas NK cell activity can be removed by pretreating effector cells with antiQa-5 + C in the appropriate strains, NC cell activity is unaffected (Lattime et al, 1981(Lattime et al, , 1982b. Since NC activity requires a long-term (18 h) assay, it was necessary to show that the pretreatment of the effector cells with anti-Qa-5 + C resulted in the elimination of NK cell activity when measured in the prolonged assay.…”
Section: Wehi-164mentioning
confidence: 96%
“…NC activity is (Sutherland & Durand, 1984;MacDonald & Sordat, 1980). against some different targets such as the WEHI-164 However, unlike solid tumours, MTS are easily dissociated sarcoma and is mediated by Thyl-cells (Lattime et al, 1982; into single cells by a mild trypsinization without loss of cell 1983). Recently it has been shown that NC activity may be viability or function.…”
mentioning
confidence: 99%
“…(DeLustro & Haskill, 1978). Natural killer (NK) cells and natural cytotoxic (NC) cells have been shown to have Tumour system spontaneous cytolytic activity against a wide variety of ET sammaysroawihaoesotnosyi tumours (Lattime et at., 1982 (Cikes et al, 1973). WEHI-164, a fibrosarcoma, prior to chromium release assay.…”
mentioning
confidence: 99%
See 1 more Smart Citation